Olaparib as Treatment Versus Nonplatinum Chemotherapy in Patients With Platinum-Sensitive Relapsed Ovarian Cancer: Phase III SOLO3 Study Final Overall Survival Results - Scambia, Giovanni; Villalobos Valencia, Ricardo; Colombo, Nicoletta; Cibula, David; Leath, Charles A; Bidziński, Mariusz; Kim, Jae-Weon; Nam, Joo Hyun; Madry, Radoslaw; Hernández, Carlos; Mora, Paulo A R; Ryu, Sang Young; et al. (Journal of clinical oncology, 2025)
Olaparib treatment significantly improved objective response rate (primary end point) and progression-free survival versus nonplatinum chemotherapy in patients with BRCA-mutated platinum-sensitive relapsed ovarian cancer in the open-label phase III SOLO3 trial (ClinicalTrials.gov identifier: NCT02282020). We report final overall survival (OS; prespecified secondary end point), post hoc OS analysis by number of previous chemotherapy lines, and exploratory BRCA reversion mutation analysis. Two hundred sixty-six patients were randomly assigned 2:1 to olaparib tablets (300 mg twice daily; n = 178) or physician's choice of single-agent nonplatinum chemotherapy (pegylated liposomal doxorubicin, paclitaxel, gemcitabine, or topotecan; n = 88). OS was similar with olaparib versus chemotherapy (hazard ratio [HR], 1.07 [95% CI, 0.76 to 1.49]; P = .71, median 34.9 and 32.9 months, respectively, full analysis set). OS with olaparib was favorable in patients with two previous chemotherapy lines (HR, 0.83 [olaparib v chemotherapy] [95% CI, 0.51 to 1.38]; median 37.9 v 28.8 months); however, a potential detrimental effect was seen in patients with at least three previous chemotherapy lines (HR, 1.33 [95% CI, 0.84 to 2.18]; median 29.9 v 39.4 months). BRCA reversion mutations might have contributed to this finding. No patient randomly assigned to olaparib with a BRCA reversion mutation detected at baseline (6 of 170 [3.5%]) achieved an objective tumor response.
Keywords: doxorubicin; topotekan; polyethylenglykoly; protein BRCA1; doba přežití bez progrese choroby; lokální recidiva nádoru; Piperazines; deoxycytidin; Antineoplastic Combined Chemotherapy Protocols; ftalaziny; Poly(ADP-ribose) Polymerase Inhibitors; Ovarian Neoplasms; Gemcitabine; piperaziny; Adult; Aged; dospělí; senioři; paclitaxel; nádory vaječníků; Paclitaxel; Topotecan; Polyethylene Glycols; Neoplasm Recurrence, Local; BRCA2 Protein; lidé; ženské pohlaví; Humans; PARP inhibitory; protokoly protinádorové kombinované chemoterapie; BRCA1 Protein; Female; Phthalazines; Progression-Free Survival; lidé středního věku; gemcitabin; Doxorubicin; protein BRCA2; Middle Aged; Deoxycytidine